A Comparison of the Efficacy and Safety of Intravenous Followed by Oral Delafloxacin With Vancomycin Plus Aztreonam for the Treatment of Acute Bacterial Skin and Skin Structure Infections: A Phase 3, Multinational, Double-Blind, Randomized Study. (6th March 2018) - O'Riordan, William; McManus, Alison; Teras, Juri; Poromanski, Ivan; Cruz-Saldariagga, Maria; Quintas, Megan; Lawrence, Laura; Liang, ShuJui; Cammarata, Sue; ,
Abstract : This phase 3 trial in acute bacterial skin and skin structure infections showed IV followed by oral delafloxacin to be noninferior to IV vancomycin/aztreonam combination therapy and well tolerated. Oral delafloxacin appears to maintain the initial response with IV delafloxacin. Abstract: Background: Delafloxacin is an intravenous (IV)/oral anionic fluoroquinolone with activity against gram-positive (including methicillin-resistant Staphylococcus aureus [MRSA]), gram-negative, atypical, and anaerobic organisms. It is approved in the United States for acute bacterial skin and skin structure infections (ABSSSIs) caused by designated susceptible gram-positive and gram-negative organisms, and is in development for the treatment of community-acquired bacterial pneumonia. Methods: A multicenter, randomized, double-blind trial of 850 adults with ABSSSI compared delafloxacin 300 mg IV every 12 hours for 3 days with a switch to 450 mg oral delafloxacin, to vancomycin 15 mg/kg IV with aztreonam for 5–14 days. The primary endpoint was objective response at 48–72 hours. Investigator-assessed response based on resolution of signs and symptoms at follow-up (day 14 ± 1), and late follow-up (day 21–28) were secondary endpoints. Results: In the intent-to-treat analysis set, the objective response was 83.7% in the delafloxacin arm and 80.6% in the comparator arm. Investigator-assessed success was similar at follow-up (87.2% vs 84.4%) and late follow-up (83.5% vs 82.2%). Delafloxacin was comparable to vancomycin + aztreonam in eradication of MRSA at 96.0% vs 97.0% at follow-up. Frequency of treatment-emergent adverse events between the groups was similar. Treatment-emergent adverse events leading to study drug discontinuation was higher in the vancomycin + aztreonam group (1.2% vs 2.4%). Conclusions: In ABSSSI patients, IV/oral delafloxacin monotherapy was noninferior to IV vancomycin + aztreonam combination therapy for both the objective response and the investigator-assessed response at follow-up and late follow-up. Delafloxacin was well tolerated as monotherapy in treatment of ABSSSIs. Clinical Trials Registration: NCT01984684.